Local audit of empiric antibiotic therapy in bacteremia: A retrospective cohort study. - Anthony D Bai; Neal Irfan; Cheryl Main; Philippe El-Helou; Dominik Mertz (PLoS ONE)
Background It is unclear if a local audit would be useful in providing guidance on how to improve local practice of empiric antibiotic therapy. We performed an audit of antibiotic therapy in bacteremia to evaluate the proportion and risk factors for inadequate empiric antibiotic coverage. Methods This retrospective cohort study included patients with positive blood cultures across 3 hospitals in Hamilton, Ontario, Canada during October of 2019. Antibiotic therapy was considered empiric if it was administered within 24 hours after blood culture collection. Adequate coverage was defined as when the isolate from blood culture was tested to be susceptible to the empiric antibiotic. A multivariable logistic regression model was used to predict inadequate empiric coverage. Diagnostic accuracy of a clinical pathway based on patient risk factors was compared to clinician's decision in predicting which bacteria to empirically cover. Results Of 201 bacteremia cases, empiric coverage was inadequate in 56 (27.9%) cases. Risk factors for inadequate empiric coverage included unknown source at initiation of antibiotic therapy (adjusted odds ratio (aOR) of 2.76 95% CI 1.27-6.01, P = 0.010) and prior antibiotic therapy within 90 days (aOR of 2.46 95% CI 1.30-4.74, P = 0.006). A clinical pathway that considered community-associated infection as low risk for Pseudomonas was better at ruling out Pseudomonas bacteremia with a negative likelihood ratio of 0.17 (95% CI 0.03-1.10) compared to clinician's decision with negative likelihood ratio of 0.34 (95% CI 0.10-1.22). Conclusions An audit of antibiotic therapy in bacteremia is feasible and may provide useful feedback on how to locally improve empiric antibiotic therapy.